Prevalence of insect pests in large cardamom (Amomum subulatum Roxb.) and evaluation of bio-rationals for the management of major pests under organic agro-ecosystem of Sikkim: Bio-rationals for the management of major pests of large cardamom - Raj, C; Singh, S; Kalita, H; Avasthe, R K; Gopi, R; Singh, M; Kapoor, C; Kumar, R; Singh, N J (Journal of Spices and Aromatic Crops, 2021)
Large cardamom (Amomum subulatum Roxb.) is one of the important cash crops of Sikkim and Darjeeling areas of West Bengal. In this study, a fixed plot survey on insect pests of large cardamom was conducted and found that stem borer (Glyphipterix spp., Lepidoptera: Glyphiperidae), shoot fly (Merochlotops dimorphus Cherian, Diptera: Chlororpidae), leaf eating caterpillar (Artona chorista Jordon, Lepidoptera: Zygaenidae) and tea mosquito bug (Helopeltis theivora Waterhouse, Hemiptera: Miridae) are the major pests of the crop. Eco-friendly organic treatments like neem-based oil, petroleum-derived horticultural oil, spinosad and different formulations of entomopathogens were tested against these major insects. Among all, application of spinosad 45 SC @ 0.3 ml L-1 was found effective followed by neem-based oil (Azadirachtin 0.15% EC) 1500 ppm @ 3 ml L-1 at three different time intervals (first application in February-March, second application in June-July and third application in October-November) against all insects. Moreover, entomopathogenic bio-control agents (Bacillus thuringiensis @ 2 ml L-1, Metarhizium anisopliae@ 5 ml L-1 and Beauveria bassiana @ 5 ml L-1) were on par with neem-based oil for the management of stem borer. Considering the economic importance of the crop and absence of valid technology for management of insect pests in large cardamom through organic options, application of either of them could be helpful in organic management of insect pests in Sikkim.